Hepatitis C virus infection propagates through interactions between Syndecan‐1 and CD81 and impacts the hepatocyte glycocalyx. (23rd December 2016) - Grigorov, Boyan; Reungoat, Emma; Gentil dit Maurin, Alice; Varbanov, Mihayl; Blaising, Julie; Michelet, Maud; Manuel, Rachel; Parent, Romain; Bartosch, Birke; Zoulim, Fabien; Ruggiero, Florence; Pécheur, Eve‐Isabelle
Abstract: The hepatitis C virus (HCV) infects hepatocytes after binding to heparan sulfate proteoglycans, in particular Syndecan‐1, followed by recognition of the tetraspanin CD81 and other receptors. Heparan sulfate proteoglycans are found in a specific microenvironment coating the hepatocyte surface called the glycocalyx and are receptors for extracellular matrix proteins, cytokines, growth factors, lipoproteins, and infectious agents. We investigated the mutual influence of HCV infection on the glycocalyx and revealed new links between Syndecan‐1 and CD81. Hepatocyte infection by HCV was inhibited after knocking down Syndecan‐1 or Xylosyltransferase 2, a key enzyme of Syndecan‐1 biosynthesis. Simultaneous knockdown of Syndecan‐1 and CD81 strongly inhibited infection, suggesting their cooperative action. At early infection stages, Syndecan‐1 and virions colocalized at the plasma membrane and were internalized in endosomes. Direct interactions between Syndecan‐1 and CD81 were revealed in primary and transformed hepatocytes by immunoprecipitation and proximity ligation assays. Expression of Syndecan‐1 and Xylosyltransferase 2 was altered within days post‐infection, and the remaining Syndecan‐1 pool colocalized poorly with CD81. The data indicate a profound reshuffling of the hepatocyte glycocalyx during HCV infection, possibly required for establishing optimal conditions of viral propagation.